CERAMIC AND METAL PROSTHESES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Ceramic and metal prostheses are widely used in modern dentistry to restore the function, aesthetics, and structural integrity of damaged teeth. The choice between ceramic, metal, or combined metal-ceramic prosthetic materials depends on several factors, including the location of the tooth, the patient’s aesthetic demands, functional requirements, and biological compatibility. Metal prostheses, typically made from alloys such as cobalt-chromium or nickel-chromium, are valued for their high strength, durability, and resistance to fracture. However, they have lower aesthetic appeal due to their metallic color, which makes them less suitable for anterior teeth